Human exposure to pollutant emissions from brick kilns and their association with ocular health and neurotoxic symptoms: a pilot study in the Refugio Brickmaking Area, León, Mexico - Pedroza Carrillo, Paula Karolina; Salazar-Gómez, Anuar; Jimenez Alcala, Ana Mariela; Nilo Olmos, Daniela del Rocío; Perez Perez, Blanca; Rocha Villa, Valeria Guadalupe; Martínez-Rodríguez, Ana Laura; Thébault, Stéphanie C.; Hernández-Zimbrón, Luis Fernando (Frontiers in Psychiatry, 2025)
León, Guanajuato, Mexico, like many other places in the world, faces significant air pollution due to emissions from artisanal brick kilns. If prolonged exposure to these pollutants has been associated with neurotoxicity symptoms and potential risks of neurodegenerative diseases, their effects on ocular health remain poorly understood. Therefore, this study evaluated the visual health, prevalence of neurotoxicity symptoms and mental health conditions, as well as potential associations in residents near the Refugio Brickmaking Region, in León, Guanajuato, Mexico. A cross-sectional study was conducted on thirteen participants working or living in brick kilns and thirteen control participants. Clinical evaluations included vital signs, uncorrected distance visual acuity (UDVA), and refraction test. A Likert scale modified version of the Q16 neurotoxicity questionnaire was used to evaluate neurotoxic symptoms and mental health conditions were identified through the clinical history. Neurotoxicity scores were compared between groups using the Mann Whitney U test, while the Chi-square test was used to assess the association between working or living in brick kilns and the prevalence of ocular and neurotoxic symptoms. The groups were paired in age (44.64 ± 16.4 vs. 52.38 ± 18.4 years-old for exposed and control groups, respectively), The alleged exposed group had an average age of 44.64 years, compared to 52.38 years in the controls). Six ocular symptoms were prevalent among participants working or living in brick kilns: foreign body sensation, blurred vision, itchy eyes, watery eyes, photophobia, and decreased visual acuity. These participants also had diminished binocular uncorrected distance visual acuity (UDVA ≥ 0.3 logMAR), and increased prevalence of myopia. Also, a positive association was found between working or living in brick kilns and reported anxiety/depression, irritability, and insomnia. These data clearly demonstrated a deterioration in eye health, in addition to an increased prevalence of neurotoxicity symptoms, in relation to working or living in brick kilns, which highlights the need for stricter regulations to safeguard workers and residents in high-risk areas.